Role of Rifaximin in Prevention of Recurrent Hepatic Encephalopathy in Chronic Liver Disease - Sahar Farzand; Abdul Latif Khattak; Rafi ud Din; Karamat Hussain Shah Bukhari; Muhammad Shahbaz Amin; Shahzeb Ahmed Satti (Journal of Bahria University Medical and Dental College, 2020)
Objectives: To determine the efficacy (in terms of recurrence) of rifaximin in Hepatic Encephalopathy (HE) in chronic liver disease. Study Design and Setting: A descriptive study carried out from 4th September 2018 to 3rd March 2019 at the department of Medicine, Combined Military Hospital, Quetta. Methodology: A total of 104 patients of chronic liver disease with HE, 25-65 years and both genders were included. Patients with gastrointestinal hemorrhage, chronic renal insufficiency and anemia were excluded. Then tab Rifaximin 550 mg twice daily along with standard prescription i.e. Lactulose 30 to 60 ml in two to three divided doses per day was given to each patient and efficacy was noted. Statistical analysis was carried out using SPSS version 20.0. Age, duration of disease and Conn’s score was presented as mean and standard deviation. A p value = 0.05 was considered as significant Results: Age range in our study was from 25 to 65 years with a mean of 45.73 ± 8.13 years. Most of the patients 54 (51.92%) were between 46 to 65 years of age range. Out of the 104 patients, 77 (74.04%) were male and male to female ratio was 2.9:1. Mean duration of disease was 13.66 ± 3.77 months. Mean conn’s score was 4.77 ± 1.43. Efficacy (no recurrence) of rifaximin in HE in chronic liver disease was found in 85 (81.73%) patients. Conclusion: It was inferred that rifaximin is useful in decreasing the recurrence of HE in chronic liver disease patients with previous episode/s of encephalopathy.